Antipsoriatic Effects of Wannachawee Recipe on Imiquimod-Induced Psoriasis-Like Dermatitis in BALB/c Mice - Mingkwan Na Takuathung (2018)
© 2018 Mingkwan Na Takuathung et al. Psoriasis is a common immune-mediated chronic inflammatory skin disease characterized by thick and erythema raised plaques with adherent silvery scales. T-cells are activated via the IL-23/Th17 axis which is involved in psoriasis pathogenesis. Conventional treatments of psoriasis have adverse events that influence patients' adherence. Wannachawee Recipe (WCR) is Thai traditional medicine that is known to be effective for psoriasis patients; however, preclinical evidence is still lacking. This study investigated the therapeutic potential of WCR on antiproliferant activity using imiquimod-(IMQ-) induced psoriasis-like dermatitis in a mouse model. Psoriasis-like dermatitis was induced on the shaved dorsal skin and right ear pinna of BALB/c mice by topical application of IMQ for 15 consecutive days after which WCR was administered to the mice by oral gavage for 10 days. Phenotypical observations, histopathological examinations, and ELISA of skin and blood samples were conducted. WCR significantly ameliorated development of IMQ-induced psoriasis-like dermatitis and reduced levels of Th17 cytokines (IL-17A, IL-22, and IL-23) in both serum and dorsal skin. Histopathological findings showed a decrease in epidermal thickness and inflammatory T-cell infiltration in the WCR-Treated groups. The WCR has pharmacological actions which regulate Th17 related cytokines suggesting that it is a potential alternative therapeutic strategy for psoriasis.